Extra neural metastasis of glioblastoma multiforme: a literature review - Shoaib, Faryal; Muhammad Furrukh; Mushtaq, Fahad; Sayeed, Sana; Nasir, Humaira; Ghafoor, Hashaam (Journal of the Pakistan Medical Association, 2023)
Extra-neural metastases of glioblastoma multiforme are uncommon with unidentified metastatic mechanism. There is no consensus over optimum treatment regimen. The current narrative review was planned to illuminate the presence criteria, sites of metastatic spread, incidence, mechanism, risk factors and management. Key Words: Glioblastoma multiforme, Extra-neural metastases, Spread, Mechanism, Risk factors.